Zein Monolayers Characterization and Interaction with (Bio)surfactants - Wojciechowski, Kamil (Langmuir : the ACS journal of surfaces and colloids, 2025)
Zein is the main protein of corn seeds, which is often employed in food packaging and as a model of keratin. In this study, zein monolayers were deposited from nonconventional solvents: aqueous ethanol and acetic acid, on pure water that was later exchanged for 1% (bio)surfactant solutions: SDS, CTAB, Triton X-100, and the saponin-rich plant extracts of soapwort (Saponaria officinalis L.) and cowherb (Saponaria vaccaria [P. Mill.] Rauschert), as well as Quillaja bark saponins (QBS). The monolayers on pure water could be reversibly compressed up to ∼47 mN/m. On the basis of neutron reflectivity (NR) results, the liquid expanded-liquid expanded (LE-LE) transition observed at π ≈ 30 mN/m was assigned to an expulsion of the well-packed monolayer initially located on the air side of the interface, toward the aqueous side. The phase transition was accompanied by an increase in the layer thickness (from ∼1 to ∼6 nm) and the adsorbed amount (from ∼1.7 to ∼5.0 mg/m2). In contrast to the saponin-rich solutions, the synthetic surfactants introduced to the subphase easily removed the zein monolayer precompressed to π0 = 30 mN/m, although the mechanism was different for the ionic (continuous displacement) and for the nonionic (orogenic-like). The zein layers at Si/water and their resistance to the detergent activity of SDS and QBS were assessed using NR, proving that the layers cast from acetic acid showed slightly higher mechanical strength than those cast from aqueous ethanol